Typy podejścia menedżerów do wdrożenia i utrzymania systemów zarządzania jakością zgodnych z normą EN ISO 9001:2000 - Wierzbic, Arkadiusz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
There are three types of managers' approaches to the level of quality management system implementation and maintenance presented in the article. The three approaches are built of respectively: activities focused on real development, activities performed to maintain the system on the secure and acceptable level from the point of view of external auditors' evaluation, and activities conducted in order to maintain the certificate with minimum effort. The fundamental features and factors taken into account by managers while choosing one of the approaches are identified and described. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 93-98